Evaluation of Universities QoS using Fuzzy Cognitive Maps - Panagiotis, Perivolaris; Vassilis, Stylianakis (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
HEIs’ digital transformation is revealing a variety of new opportunities for improving not only their current online teaching practices but also their overall business operations. The processing of data can be further expanded using a range of advanced techniques, as is the case of cognitive tree maps, fuzzy networks, or even evolutionary algorithms, to examine and explain how the behaviour of a complex system, such as an HEI, is affected by the multiple conditions changing over time. The design of such a tool and the development of an optimization system that can determine ideal values for these aspects are covered in the proposal. The present work introduces a tool for the evaluation of the HEI Quality of Service factor (HEI-QoS), using a Fuzzy Cognitive Map designed for a specific purpose. The FCM model uses eight concepts which characterize the HEI operation and performance, taking into consideration the most well- known HEI rankling tools. Concepts values can be estimated from a field research analysis inside the HEI resulting in a very useful internal evaluation tool for a HEI.